2021
DOI: 10.3892/ol.2021.12956
|View full text |Cite
|
Sign up to set email alerts
|

miR‑425 regulates lipophagy via SIRT1 to promote sorafenib resistance in liver cancer

Abstract: Liver cancer is one of the most malignant cancer, with poor outcomes and a high incidence rate, and current treatment approaches to prevent tumor progression and development remain unsatisfactory. Therefore, it is urgent to explore novel methods to inhibit tumor growth and metastasis. Autophagy is a highly conserved process associated with metastasis and drug resistance. Lipids are selectively recognized and degraded via autophagy; thus, autophagy is a crucial process to maintain tumor self-protection. MicroRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The last study showed that miR-425 regulates SIRT1 in HCC. When miR-425 is inhibited, SIRT1 promotes fat autophagy by mediating the autophagy process and promoting sorafenib resistance [29]. Additionally, SIRT1 promotes gene mutations to induce drug resistance in cancer cells [30].…”
Section: Overview Of Sirtsmentioning
confidence: 99%
“…The last study showed that miR-425 regulates SIRT1 in HCC. When miR-425 is inhibited, SIRT1 promotes fat autophagy by mediating the autophagy process and promoting sorafenib resistance [29]. Additionally, SIRT1 promotes gene mutations to induce drug resistance in cancer cells [30].…”
Section: Overview Of Sirtsmentioning
confidence: 99%